Cheaper by the dozen - Gilbreth, Frank Bunker 1911-2001; Carey, Ernestine Gilbreth 1908-2006 (Crowell, 1948)
Reminiscences of the Gilbreth family
Hier auch später erschienene, unveränderte Nachdrucke
Reminiscences of the Gilbreth family
Keywords: Gilbreth, Frank Bunker / 1868-1924; Gilbreth, Lillian Moller / 1878-1972